Implementation of Community Empowerment Policy Through Sustainable Tourism Development, Indonesia - Sudirman M; Fatmawati A. Mappasere; Nuryanti Mustari (Universitas Merdeka Malang, 2025)
Sustainable tourism has emerged as a global strategy for promoting economic growth and poverty alleviation. This study aims to analyze the implementation of existing policies, identify the supporting and inhibiting factors affecting policy implementation, and assess the impacts of sustainable tourism development. A qualitative research method was employed, with data collected through interviews and observations, in an effort to understand the implementation of community empowerment policies through sustainable tourism as a solution for local economic development in Pangkep Regency.The data collected both through direct sources and online platforms—were analyzed using the “Concept Map” feature in the NVivo 12 Plus application. The findings indicate that the implementation of community empowerment policies through sustainable tourism in Pangkep Regency has made notable progress, although certain challenges persist, such as budget limitations and unequal access to training. Key supporting factors include effective promotional efforts, adequate infrastructure, simplified business licensing procedures, and human resource development programs. On the other hand, the main obstacles consist of limited financial resources, low public awareness, and bureaucratic inefficiencies. The policy has shown a positive impact on the tourism sector and the overall well-being of the local population by promoting cultural preservation, generating employment opportunities, and strengthening micro, small, and medium enterprises (MSMEs). The primary recommendations emphasize the importance of adequate funding, capacity-building programs, and strong collaboration among government entities, local communities, and relevant sectors to ensure the long-term sustainability of tourism development